The Practice of Physical Activity After Breast Cancer Treatments: A Qualitative Study Among Portuguese Women - Sequeira, Margarida; Luz, Rita; Alvarez, Maria-João (Frontiers in Psychology, 2022)
Background: Women survivors of breast cancer treatments face significant challenges around initiation or maintenance of physical activity (PA) as they transit to recovery. Embracing their needs and preferences is important to increase adherence. This study aimed to explore the perspectives of Portuguese women survivors of breast cancer regarding regular performance of PA and individual choices and strategies that should be considered in designing effective interventions. Methods: The individual semi-structured interviews (N=20) were analyzed through thematic analysis, following an inductive process, seeking to identify the barriers, facilitators, and particular influencing circumstances associated with regular PA. Results: Four themes and several contextual, emotional, physical, and social factors were identified as determinants of regular PA. Guilt, women’s duties, and altruism to help close relatives were identified as emotional and cultural factors that are less-found in the existing literature. PA showed influence both from health professionals’ counseling and from knowledge and beliefs held by these women. Conclusions: While confirming the already-known impact of breast cancer diagnosis and treatments on PA, which redefine participants’ availability to be active, the findings highlight beliefs and specific emotional factors that should be considered when planning culturally sensitive interventions.